1984
DOI: 10.1016/0014-5793(84)80055-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregating activity of lysophosphatidic acids is not related to their calcium ionophore properties

Abstract: The calcium ionophore properties of A23187 and of two lysophosphatidic acid (LPA) analogs (1‐palmitoyl‐ and 1‐hexadecyl‐sn‐glycero‐3‐phosphate or P‐GPA and H‐GPA, respectively) were compared using platelet membrane vesicles loaded with 45Ca. Half maximal effect (HME) was obtained at 5 μM and 10 μM for H‐GPA and P‐GPA, respectively, against 0.7 μM for A23187, which released 2 times more Ca. The three compounds also induced platelet aggregation with a HME at 0.5 μM, 0.3 μM and 0.01 μM for A23187, P‐GPA and H‐GPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The contrasting effects of Oco2Gro and PMA on thrombin versus collagen-induced arachidonate release, with pre-incubation times of up to 5 min, may be related to the significant inhibition of thrombin-induced elevation in [Ca2+Ii levels by Oco2Gro and PMA, and the different [Ca2+Ii requirements for thrombin and collagen in the induction of arachidonate release [20,351. Thus, previous studies [20] as well as the results of the present study, have demonstrated the ability of collagen to induce arachidonate release without a rise in [Ca2+Ii levels, while this is not the case with thrombin [35]. On the other hand, potentiation of Ca2 +-ionophoreinduced arachidonate release by PMA [21] and Oco2Gro suggests that the effect of C kinase activators on agonistinduced arachidonate release may depend on two factors : firstly, on whether arachidonate release is dependent on [Ca2 ' Ii mobilisation, and secondly, whether [Ca2 +Ii mobilisation is inhibited by them.…”
Section: Discussionsupporting
confidence: 67%
“…The contrasting effects of Oco2Gro and PMA on thrombin versus collagen-induced arachidonate release, with pre-incubation times of up to 5 min, may be related to the significant inhibition of thrombin-induced elevation in [Ca2+Ii levels by Oco2Gro and PMA, and the different [Ca2+Ii requirements for thrombin and collagen in the induction of arachidonate release [20,351. Thus, previous studies [20] as well as the results of the present study, have demonstrated the ability of collagen to induce arachidonate release without a rise in [Ca2+Ii levels, while this is not the case with thrombin [35]. On the other hand, potentiation of Ca2 +-ionophoreinduced arachidonate release by PMA [21] and Oco2Gro suggests that the effect of C kinase activators on agonistinduced arachidonate release may depend on two factors : firstly, on whether arachidonate release is dependent on [Ca2 ' Ii mobilisation, and secondly, whether [Ca2 +Ii mobilisation is inhibited by them.…”
Section: Discussionsupporting
confidence: 67%
“…So our present study confirms and extends these data by showing that PLC activation occurs in vivo at basal [Ca2+]i, which appears to be sufficient for the enzyme to operate. In addition to our recent work on the properties of lysophosphatidic acids [37], this would give further support to the hypothesis that PLC together with protein kinase C are involved in cell activation through a Ca2+-independent pathway [l l-131. It also fits with the proposed role of inositol-tri-phosphate, the liberation of which by PLC would trigger Ca*+ mobilization from an intracellular store [9].…”
Section: Discussionsupporting
confidence: 57%
“…These authors identified LPA as being one of the active factors and noted that it caused desensitization of the platelet response, a hallmark of GPCR action. Simon et al discovered that the alkyl-ether analogue of LPA is a potent activator of human platelets at concentrations as low as 10 -10 M, making this analogue nearly as potent as platelet-activating factor (Simon et al, 1982;1984). The barrier function of vascular endothelial cells is altered by LPA (Schulze et al, 1997;Alexander et al, 1998;English et al, 1999), and LPA induces the expression of VCAM-1 and E-selectin on the surface of cultured human endothelial cells (Rizza et al, 1999).…”
Section: Lpa In Reproductive Disordersmentioning
confidence: 99%